Pandangan Hukum Islam Terhadap Fungsi Jaminan Dalam Pembiayaan Muḍārabah (Studi Kasus Di Kjks Bmt Surya Madani Boyolali) - Asia, Siti Nur; , Dr. M. Muhtarom, SH. MH (2016)
In economic context, BMT as an institution of fund distribution is attempting to channel appropriately the fund that has been collected in order to meet the needs of people. On one side, persons with more funds will save their funds in LKS (Islamic Financial Institution), and on other hand,there are persons with less fund but they have strong determination and capability to make businesses for living. These raise a partnership agreement so that the fund can be distributed and it can make wellbeing into reality and to obtain blessing. According to fatwa of MUI (Council of Indonesian Islamic Scholars), muḍārabah financing is trustworthiness in nature. The agreement needs a high level of honesty and upholds justice between the two parties. Therefore, each party must keep mutual interest. It means the Ṣāḥibul Māl cannot require Muḍārib to provide collateral, because Muḍārib is only a capital manager. Fiqh does not say that collateral is one of requirements in the agreement. It is encouraging author to do a deep research on "Islamic viewpoint on collateral function in muḍārabah financing (a case study in KJKS BMT Surya Madani of Boyolali). Purpose of the research is to obtain understanding about function of collateral required in muḍārabah financing applied in muḍārabah financing of KJKS BMT Surya Madani of Boyolali, and to get information on Islamic viewpoint on collateral function in muḍārabah financing. The research is a field research with descriptive-qualitative approach. Method of data collection has used observation, interview and documentation. The data has been analyzed descriptively. Based on results of the research, it can be concluded that collateral requirement applied in muḍārabah financing of BMT Surya Madani is in accordance with Islamic Law, because the collateral function is to protect Ṣāḥibul Māl from risk of failure in part of Muḍārib and to protect fund provided by BMT to Muḍārib, considering the fund is not exclusive property of the BMT but it is public property. And the collateral can be sold as exchange of the fund that is failed to repay if it is proved that Muḍārib has made error intentionally, negligence or failed to satisfy the agreement.